Requirement of a detailed specification of the proposed changes to the territorial division of the state in the question in the local referendum (Discourse of Law and Administration, 2022)
In relation to the question in a local referendum on the creation, merger, division and removing a commune and establishment of the commune’s borders, the legislator, next to the requirements, which must be met by “every” referendum question, introduced a specific requirement. According to the requirement the referendum question contained in the inhabitants’ application for the referendum should specify in detail the proposed changes in the territorial division of the state. At the same time, the legislator did not specify how this “detailed” definition of the proposed changes should be understood. The article presents how this particular requirement is perceived in the legal doctrine and, above all, in the jurisprudence of administrative courts. Based on the jurisprudence, it was determined in particular which elements such a question must contain, and for which the inclusion in the question depends on the will of the referendum initiator, as well as with the participation of and according to which criteria the referendum question is assessed in the analyzed case.
Keywords: local referendum; changing the communes’ border; question in a local referendum